A Morphological Analysis of Derivational Suffix in the Short Story “How to Become a Writer” by Lorrie Moore - Hutasoit, Mikhael Parlindungan (Transpublika Publisher, 2025)
The limited understanding of English word formation processes among language learners constitutes a persistent impediment to vocabulary acquisition and textual comprehension. This study examines the deployment of derivational suffixes in Lorrie Moore's short story